Innovation policy for welfare services in a Swedish context - Wihlman, Thomas; Sandmark, Hélène; Hoppe, Magnus (Scandinavian Journal of Public Administration, 2012)
The aim of the study is to explore the role of public welfare services expressed in the Swedish government’s innovation policy. The focus is on municipal and county services, such as education and health care. The study is based on an analysis of 55 documents produced by the government and its agencies. Although innovation policy is a major issue in Sweden, and Sweden has a large public sector, research on innovation within this field is very limited. The results show that the municipality and county services are visible in innovation policy when they are a driving force for innovation in the private sector. This applies especially when public procurement becomes a vehicle for business innovation. Innovation is not used as a concept representing radical change and general progress of the public sector as such. When municipal welfare services become visible in the studied documents, there are often references to a need for efficiency improvements and for procurement leading to innovation. For the public sector, including local welfare services, no coherent innovation policy is present, but this study found elements that could become part of an innovation policy. Policy development is important for the future, considering the public sector ́s role in the important and increasing service sector and in the society as a whole.